Local Knowledge on the Use of Swertia chirayita as Traditional Medicine: Conservation challenges in Sikkim Himalaya, India - Pradhan, Bharat K.; Badola, Hemant K. (Ethnobotany Research and Applications, 2015)
Swertia chirayita (Roxb.) Buch.-Ham. ex C.B.Clarke (Gentianaceae) has been used as a traditional medicine, but this knowledge is eroding with modernization.This study attempted to understand the perception and knowledge of people about the species use and conservation in four districts of Sikkim Himalaya. A questionnaire survey was used for data collection. Swertia chirayita is highly used for treating fever and cold and cough by both male (p <0.001; F = 63.72) and female (p <0.001; F = 86.16) respondents. Over 92% of respondents administer the species, as medicine, orally in the form of decoction. The perception on the market potential of S. chirayita was significantly high amongst both male (p <0.001; F = 39.27) and female (p <0.001; F = 30.46) respondents. In Sikkim, a majority of respondents (p <0.05) consider habitat destruction and human disturbances as the chief causes of natural population decline of S. chirayita.